THE INFLUENCE OF DIFFERENT MODELS OF SWIMMING TRAINING (DEFINED IN RELATION TO ANAEROBIC THRESHOLD) ON THE CHANGE OF VARIABLES OF BODY COMPOSITION - Dragan Krivokapić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
On the sample of 32 fourth grade students of some Belgrade highs schools, who had the physical education classes carried out at the city's swimming pools, an attempt was made to evaluate the effects of the two different programmes of swimming training in different intensity zones, defi ned relative to the anaerobic threshold. The subjects were the examinees were divided into two groups out of 15 i.e. 17 participants who were not (according to statistics) signifi cantly different in terms of observed anthropometric dimensions and relative indexes of body compositionThe fi rst training model consisted of swimming at the intensity level within, theat a higher intensity sometimes surpassing the anaerobic threshold. The experimental programme with both sub-groups lasted 8 weeks with 3 training sessions per week, 2 of which were identical for both experimental groups, with the third one differing regarding the swimming intensity, this in the fi rst group being still in the zone below, and in the second group occasionally in the zone above the anaerobic threshold. The amount of training and the duration were the same in both programmes. The aim of the research was to evaluate and to compare the effects of the two training models, using as the basic criteria possible changes of observed anthropometric dimensions and relative indexes of body composition. Although the difference in effi ciency of applied experimental programmes is not defi ned, we can claim that the systematic differences that appeared between the initial and the fi nal evaluation in both groups consisted of: changes of body weight, thickness of abdominal skin and fat tissue, both in relative and absolute terms.